1989
DOI: 10.1111/j.1365-2125.1989.tb03522.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine fails to attenuate haemodynamic tolerance to glyceryl trinitrate in healthy volunteers.

Abstract: 1 The effects of chronic dosing with N-acetylcysteine (NAC), on nitrate-induced haemodynamic changes during the acute and chronic treatment of healthy volunteers with glyceryl trinitrate (GTN) patches (Transiderm nitro) has been investigated. 2 Seven volunteers were treated in a double-blind randomised crossover manner for two periods of 4 days with 20 mg of transdermal GTN/24 h together with NAC (200 mg three times daily) or matching placebo. There was a washout period of >3 days between treatment periods.3 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
2
4
0
Order By: Relevance
“…In contrast to the other antioxidants tested, the sulphydryl donor N‐acetyl‐L‐cysteine was able to abolish tolerance development to the lowest level of GTN, while clearly tending to attenuate tolerance to the higher level. While a number of previous studies have failed to find improvement with N‐acetyl‐L‐cysteine in tolerant animals (Abdollah et al , 1987; Hütter et al , 1988; Münzel et al , 1989; Holtz et al , 1989) or man (Hogan et al , 1989), the present observations are in agreement with the results of Lawson et al (1991) and Newman et al (1990) that N‐acetyl‐L‐cysteine mitigates nitrate tolerance both in vitro and in vivo. Furthermore, given that N‐acetyl‐L‐cysteine was washed out before vasorelaxation to GTN was studied, the beneficial action of N‐acetyl‐L‐cysteine in the rat isolated aorta is clearly distinguishable from a simple reversal of tolerance due to the extracellular metabolism of GTN (see Fung et al , 1988; Levy et al , 1988; Hütter et al , 1988; Boesgaard et al , 1991).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the other antioxidants tested, the sulphydryl donor N‐acetyl‐L‐cysteine was able to abolish tolerance development to the lowest level of GTN, while clearly tending to attenuate tolerance to the higher level. While a number of previous studies have failed to find improvement with N‐acetyl‐L‐cysteine in tolerant animals (Abdollah et al , 1987; Hütter et al , 1988; Münzel et al , 1989; Holtz et al , 1989) or man (Hogan et al , 1989), the present observations are in agreement with the results of Lawson et al (1991) and Newman et al (1990) that N‐acetyl‐L‐cysteine mitigates nitrate tolerance both in vitro and in vivo. Furthermore, given that N‐acetyl‐L‐cysteine was washed out before vasorelaxation to GTN was studied, the beneficial action of N‐acetyl‐L‐cysteine in the rat isolated aorta is clearly distinguishable from a simple reversal of tolerance due to the extracellular metabolism of GTN (see Fung et al , 1988; Levy et al , 1988; Hütter et al , 1988; Boesgaard et al , 1991).…”
Section: Discussionsupporting
confidence: 92%
“…The present study differed from the previous two studies in that it addressed the question whether oral administration of N-acetylcysteine might prevent the development of tolerance during transdermal glyceryl trinitrate treatment of patients with chronic stable angina. In this respect it is similar in design and findings to a previous report by us investigating the effects of N-acetylcysteine on nitrate tolerance in healthy volunteers (Hogan et al, 1989).…”
Section: Discussionsupporting
confidence: 86%
“…On this basis, prevention of reversal of nitrate tolerance might be achieved by repletion of sulphydryl groups from an exogenous source such as N-acetylcysteine. This has been demonstrated in vitro (Needleman et al, 1973) but in vivo studies have given conflicting results (Hogan et al, 1989;Packer et al, 1987;Parker et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this proposal, supplementation with sources of sulphydryl groups has been shown to suppress tolerance to glyceryl trinitrate (GTN), for example (see Katz, 1990;Newman et al, 1990). However, it should be noted that other studies have not confirmed these results (Gruetter & Lemke, 1983;Stewart et al, 1988;Hogan et al, 1989). Nonetheless, sulphydryl depletion as an explanation for organic nitrate tolerance has led to the proposal that sulphydryl-containing angiotensinconverting enzyme (ACE) inhibitors might be particularly useful in conjunction with organic nitrates, since they could combat both the biochemical and physiological bases of tolerance (Katz, 1990).…”
Section: Introductionmentioning
confidence: 95%